If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x+6/2-4x-8/9=8x-8/3
We simplify the equation to the form, which is simple to understand
10x+6/2-4x-8/9=8x-8/3
Simplifying:
10x+3-4x-8/9=8x-8/3
Simplifying:
10x+3-4x-0.888888888889=8x-8/3
Simplifying:
10x+3-4x-0.888888888889=8x-2.66666666667
We move all terms containing x to the left and all other terms to the right.
+10x-4x-8x=-2.66666666667-3 + 0.888888888889
We simplify left and right side of the equation.
-2x=-4.77777777778
We divide both sides of the equation by -2 to get x.
x=2.38888888889
| 2(7x-1)=96 | | 4x-x+3y-y= | | -7(6v+5)=91 | | -6a+5(1-2a)=101 | | -10x+3y-4xy+5= | | 2k^3-36k^2=162k | | -3x+5y+3+3x-5y= | | -45=3n+9 | | (x-(2+3i))(x-(2-3i))=0 | | -5+7x-2+3x+y-8y+6= | | 10r+8=-182 | | -3xy+3xy= | | 2x+2=-2x+6 | | 2x+2=x-1 | | 5z/8=85 | | -9=x-2 | | -6(1-3x)-5x=85 | | 25x+y=13x-y | | -2+5(4n+7)=173 | | -11y^2-27=0 | | r-36=14.7 | | 250Q-2-2.5+1Q=0 | | h^2+81=0 | | 4r+r=44r+12 | | 4(x-8)=2(2-4y) | | -3=-5+x/10 | | y-3x=14 | | 250Q-2-2.5Q+1Q=0 | | 4-8b=12 | | 2(x+5)=5 | | 8t+45=175.4 | | 4x^2-13x-27= |